Healthcare professionals’ experiences of delivering sexual and reproductive health services to adolescents: A literature review - Abdul Hamid, Siti Hazariah (2019)
This literature review outlines the process of searching for relevant evidence-based literature related to the provision of sexual and reproductive health (SRH) to adolescents both in Malaysia and worldwide. This review was conducted systematically to illuminate the gap in knowledge and practice that highlights the relevance of future study in Malaysia. The search was limited to English and Malay language peer-reviewed articles published between 2002 and 2018. A total of 32 relevant articles were identified and reviewed. These studies were conducted in Africa, Europe, Asia, the United States of America, Oceania and in Muslim countries such as Egypt, Iran, Turkey and Malaysia. The general focus of the included studies was the experiences and views of healthcare professionals (HCPs), including their knowledge and attitudes in providing SRH information, contraception, emergency contraception, abortion care, confidentiality and improving adolescents’ uptake of health services. This review suggested the potential tensions that exist between the desire to prevent unwanted pregnancies and the provision of effective and adolescent-friendly SRH services in societies that disapprove of adolescents’ premarital sexual activity, contraception use and abortion services.